SOSIALISASI URGENSI ADMINISTRASI KEPENDUDUKAN BAGI WARGA MENURUT UU NO. 24 TAHUN 2013 - Rudatyo Rudatyo; Suharno Suharno; Hadi Mahmud; Ismiyanto Ismiyanto; Suparwi Suparwi; Amir Junaidi (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Community service is very important to do as one of the implementation of the “tridharma” of higher education as the main task of lecturers. The implementation of community service in Telukan Village, Grogol District, Sukoharjo Regency has been carried out on Sunday, March 27, 2022. The purpose of this community service is very noble, namely explaining the importance of public awareness, especially Telukan Village to be able to understand, understand and be able to carry out population administration in accordance with Law No. 24 of 2013 concerning population administration, both rights and obligations as law-abiding Indonesian citizens. The community service method was carried out by gathering community members at the Telukan village hall, the first event was opened by the Telukan village head and continued with material exposure by the community service team at the Faculty of Law, Islamic Batik University of Surakarta. The results that have been achieved in the implementation of community service in Telukan Village include: not all residents understand the importance of population administration, because most of the housewives who usually take care of population administration are fathers and fathers. What is very good is the participation of the community to attend, listen and hope that it will be conveyed to the head of the household for follow-up.